Lateral ventricle ectopic schwannoma: Case report and literature review - Li, Yujian; Yang, Xiang; Zhou, Huiqing; Zheng, Jun; Hui, Xuhui; Li, Hao; Liu, Yanhui (Frontiers in Oncology, 2023)
Background Cases of lateral ventricular ectopic schwannomas (LVES) are extremely rare, with only 23 cases reported thus far. This study aimed to obtain a better understanding of the disease. Methods We reported a rare case of LVES, in which the patient was admitted to our hospital, and reviewed the relevant literature on LVES to summarize and analyze the clinical manifestations, pathologies, imaging features and progress. Results Of the 23 patients, LVES was more common in men (74%, 17/23) than in women and was mostly located on the right side (78%, 18/23). The average age at clinical presentation was 28 years, with an age range between 8 and 68 years. Moreover, most cases were histologically benign, except in one case of malignancy. In all the benign cases, there were 2 cases of subtotal resection, but no recurrence was found during follow-up. Conclusions The origin of LVES could be the tumor transformation of autonomic nerve tissue in the perivascular choroid plexus. For lateral ventricle tumors,which are rare benign lesions with good prognosis after surgical resection, LVES should be considered in the differential diagnosis. Moreover, whether LVES could be considered for gamma knife treatment, similar to a small acoustic neuromas,requires further investigation.